A Comparative Analysis of Selection Criteria of Candidates in Belgium - Vandeleene, Audrey; van Haute, Emilie (Frontiers in Political Science, 2021)
The literature on candidate selection has focussed extensively on the degree of inclusiveness and decentralization of the selectorate, as part of the debate on intra-party democracy. However, much less attention has been paid to the degree of openness of candidacies, or selection criteria within parties. Yet parties have a lot of leeway in how they design selection criteria internally. Which guidelines do parties follow when making the crucial choice on which candidates to select for elections? This paper investigates selection criteria from two perspectives: the formal rules set by parties that restrict the candidate’s pool and the (informal) preferences of selectors that shape who gets selected. We aim first at contrasting the degree of party institutionalization and parties’ formal rules in candidate selection and so, we shed light on whether parties formalise their candidacy requirements and candidate selection processes to the same extent as other party activities. Second, the paper investigates the role of the selectorates, and how selectorate’s characteristics matter for the kind of (informal) selection criteria, be they intended at maximizing offices, votes or policies. Drawing on party statutes coded in the Political Party Database (PPDB) and 23 in-depth interviews with selectors, we study three francophone Belgian parties that differ both in terms of inclusiveness of the selectorate who has the final say on candidate selection and in terms of degree of centralisation, and in terms of party institutionalisation: the green party (Ecolo), the socialist party (PS), and the liberal party (MR). Our comparative analysis of parties, selection criteria provides new insights into the secret garden of politics and highlights in particular the major impact of parties, degree of centralization.